The role of macronutrients in the implementation of the corrective effect of low-mineralized water in experimental metabolic syndrome - Anatoliy Gozhenko; Nataliia Badiuk; Boris Nasibullin; Sergey Gushcha; Olena Gozhenko; Valentina Vasyuk; Yana Kutsenko; Radosław Muszkieta; Walery Zukow (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Metabolic Syndrome (MS) is a widespread pathological condition, a group of interconnected metabolic disorders that contribute to the development of a number of severe noncommunicable diseases. Natural mineral waters of various compositions are widely used in the correction of MS. Their biological activity and specificity of action is associated with the presence of specific components (micronutrients, biologically active substances). At the same time, many researchers do not pay enough attention to the role of the biological activity of macro nutrients in low mineralized mineral waters. Objective. To assess the corrective effect of macro-components of mineral waters based on a comparative analysis of changes in the structure of internal organs of white rats with the MS model, receiving mineral waters of the same balneological type, but with different quantitative composition of macro components. Materials and methods. The material for histological and histochemical tests were the internal organs of male white rats with body weight 280-320 g. Animals were ranked into 4 groups: I - rats served as a control, ӀӀ - rats with a model of MS; ӀӀӀ and ӀV - rats received the mineral waters against the background of MS modeling. The mineral waters used in the work were characterized by an increased (in close amounts) content of organic substances (C org.), similar in chemical but different in quantitative macro-component composition. At the same time, mineral waters practically did not differ in terms of total mineralization. Modeling of MS was carried out for 60 days by replacing 10% fructose solution in drinking water bowls, introducing white bread crackers into the diet, and excluding green mass from the diet. In groups where animals were corrected for MS, mineral waters were administered with an intragastric tube with olive at a dose of 1% of body weight daily, starting from the 60th day of the experiment, for 12 days. Upon completion of the experiment on day 72, histological sections (which were stained with hematoxylin-eosin) were prepared from the extracted pieces of the heart, stomach, liver and kidneys tissues. The succinate-dehydrogenase (SDH) and lactate-dehydrogenase (LDH) activity were determined on the prepared cryostat sections. Using a light microscope, changes in the structure of the above organs and changes in the activity of oxidative-restorative enzymes were evaluated. Results. The activity of oxidative-restorative enzymes was approaching normal; some manifestations of changes in water metabolism in the animal organism persisted. At the end of the use of both mineral waters, a significant decrease was found in the content of visceral fat around the intestines, renal capsule, under the pericardium, which correlated with a decrease in the animal's body weight and restoration of the fasting blood glucose level to the cereal level. The authors believe that the established features of the corrective effect of both mineral waters on changes in the structure of internal organs are explained not so much by the difference in the content and ratio of the bioactive component (C org.), but by differences in the content of macronutrients. In mineral waters obtained by rats of group III, the content of Cl- and SO4+2 ions is 2.30 and 3.67 times, and Ca2+ and Мg2+ ions are 2.75 and 4.57 more than in mineral waters, which received rats of group IV. However, the content of HCO3-, Na+, K+ is 1.14 and 1.30 times higher in the mineral waters obtained by rats of group IV. Conclusions. The authors believe that the macronutrients involved in the implementation of MWs biological activity affect the metabolic background of the organism, which creates the bioactive element - C org. conditions for the performance of more intensive corrective action.